Korelasi Minat dan Kebiasaan Menonton Anime dengan Kemampuan Menyimak Bahasa Jepang UNNES Angkatan - Wardani, Hayyin Fatika; Setiawati, Ai Sumirah (Undiksha Press, 2024)
Anime is one of the media that can be used to learn Japanese. This study aims to determine correlation between interests and habits of watching anime with ability to listen Japanese in PBJ UNNES students class of 2021. The research method used is descriptive quantitative with a sample of 30 people. Data collection techniques using questionnaires and tests.The results showed that (1) students’ interest in watching anime was in the high category while their habit of watching anime was in the low category.(2) there is a positive and significant correlation between interest in watching anime and the ability to listen Japanese. (3) there is a positive and not significant correlation between habit of watching anime and ability to listen Japanese. (4) there is a positive and significant correlation between interest and anime viewing habits, together with ability to listen Japanese as indicated by the correlation coefficient value at the 5% significance level, which is equal to (0.466) which indicates a moderate correlation level.